2012
DOI: 10.1016/j.surfcoat.2012.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission analysis on tensile failure of air plasma-sprayed thermal barrier coatings

Abstract: An acoustic emission technique was used to monitor the cracking behavior and fracture process of thermal barrier coatings subjected to tensile loading. Acoustic emission signals were extracted and preformed by fast Fourier transform, and their characteristic frequency spectrums and dominant bands were obtained to reveal fracture modes. Three different characteristic frequency bands were confirmed, corresponding to substrate deformation, surface vertical cracking and interface delamination, with the aid of scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…This method transforms the AE signals from time domain to frequency domain, and extracts the message reflecting the AE source [28]. The frequency spectrum of AE signals are strongly dependent on the failure modes of materials, but are almost independent of the failure size and operating pressure [23,28].…”
Section: Discrimination Of the Damage Modes For The Tbcs Under High Tmentioning
confidence: 99%
See 2 more Smart Citations
“…This method transforms the AE signals from time domain to frequency domain, and extracts the message reflecting the AE source [28]. The frequency spectrum of AE signals are strongly dependent on the failure modes of materials, but are almost independent of the failure size and operating pressure [23,28].…”
Section: Discrimination Of the Damage Modes For The Tbcs Under High Tmentioning
confidence: 99%
“…This method transforms the AE signals from time domain to frequency domain, and extracts the message reflecting the AE source [28]. The frequency spectrum of AE signals are strongly dependent on the failure modes of materials, but are almost independent of the failure size and operating pressure [23,28]. Previous studies indicated that the surface vertical cracks, sliding interface cracks, and opening interface cracks correspond to the characteristic frequency bands of 0.20-0.25 MHz, 0.25-0.32 MHz, and 0.4-0.45 MHz, respectively [16,23,28,29].…”
Section: Discrimination Of the Damage Modes For The Tbcs Under High Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling rate of the camera was set as one image per second. The detailed information was described in our previous works [27,[33][34][35][36]. In order to observe the crack nucleation and propagation patterns clearer,a telephoto lens with an optical enlargement factor of 200X was equipped in front of the camera, as shown in Fig.…”
Section: Senb Testsmentioning
confidence: 99%
“…Therefore, the evolution of mechanical, physical and chemical properties of 8YSZ coatings during thermal cycling plays an important role in predicting their durability and reliability. In recent years, various experimental methods such as tension [7][8][9][10][11], indentation [12][13][14][15][16], compression [17], shear [18], double cantilever beam [19] and bending tests [20][21][22][23] have been developed to measure the fracture strength and toughness of 8YSZ coatings as well as the interface adhesion strength of a TBC system. Due to the influence of bond coat, substrate and components with complicated structures, however, it is difficult to thoroughly study the mechanical properties of deposited 8YSZ top coatings.…”
Section: Introductionmentioning
confidence: 99%